IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILTY (CSR) SEBAGAI MODEL MANAJEMEN PERUSAHAAN DALAM MENCAPAI KEUNGGULAN KOMPETITIF - Dede Jaelani (GoAcademica Research dan Publishing, 2021)
A business's response to a crisis must be through inclusion in its mission to create social value beyond economic value for shareholders. However, CSR is not about how benefits are shared but about how they are created; Therefore, CSR should be seen as a new management model and not as a marketing tool. Incorporating CSR in organizations requires the integration of philosophies and principles at all levels. This article aims to explore the concept of CSR and its dimensions, in dialogue with stakeholders, in various management instruments in terms of corporate responsibility, and the value of its strategy; in such a way that companies that successfully align their interests and implement responsible environmental accounting, will achieve a competitive advantage that is difficult to imitate.